Problems Faced by Business Administration Students in English Language Skills at Politeknik Kotabaru - Rahmawardani Rahmawardani; Ibnu Faozi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aims to analyze the problems faced by Business Administration students in mastering English language skills. English proficiency is an important competency that Business Administration students must possess to support academic and professional needs in the era of globalization. However, many students still encounter various difficulties in learning English. This study employed a descriptive qualitative method. The participants consisted of 30 fourth-semester Business Administration students. Data were collected through observation, interviews, and documentation. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings revealed that students experienced difficulties in speaking, listening, reading, writing, vocabulary, pronunciation, and grammar. The most dominant problems were limited vocabulary mastery, lack of self-confidence in speaking, difficulties in understanding English conversations, pronunciation errors, and weak grammatical competence. The factors influencing these problems were categorized into internal and external factors. Internal factors included low learning motivation, lack of self-confidence, and limited vocabulary, while external factors included limited opportunities to practice English, lack of a supportive English-speaking environment, and less varied teaching methods. The study concludes that difficulties in mastering English skills remain a significant challenge for Business Administration students. Therefore, improvements are needed through more communicative learning approaches, continuous practice, and a supportive learning environment.